Pituitary and liver selenoprotein transcriptome profiles of grazing steers and their sensitivity to the form of selenium in vitamin-mineral mixes - Li, Qing; Chen, Kuey C.; Bridges, Phillip J.; Matthews, James C. (Frontiers in Animal Science, 2022)
Many supplemental Se-dependent metabolic effects are mediated through the function of selenoproteins. The full complement and relative abundance of selenoproteins expressed by highly metabolic cattle tissues have not been characterized in cattle. The complement and number of selenoprotein mRNA transcripts expressed by the pituitary and liver of healthy growing beef steers (n = 7 to 8) was characterized using NanoString methodology (Study 1). Of the 25 known bovine selenoproteins, 24 (all but SELENOH) were expressed by the pituitary and 23 (all but SELENOH and SELENOV) by the liver. Transcript abundance ranged (P ≤ 0.05) over 5 orders of magnitude in the pituitary (> 10,000 for GPX3, < 10 for DIO1 and GPX2) and liver (> 35,000 for SELENOP, < 10 for DIO2). Also unknown is the sensitivity of the selenoprotein transcriptome to the form of supplemental Se. The effect of form of supplemental Se on the relative content of selenoprotein mRNA species in the pituitary and liver of steers grazing a Se-deficient (0.07 ppm Se) tall fescue pasture and consuming 85 g/d of a basal vitamin-mineral mix that contained 35 ppm Se as either (n = 6 to 8) ISe, organically-bound Se (SELPLEX, OSe), or a 1:1 blend of ISe and OSe (Study 2) was determined by RT-PCR after sequence-validating the 25 bovine selenoprotein cDNA products. In the pituitary, Se form affected (P < 0.05) the relative content of 9 selenoprotein mRNAs and 2 selenoprotein P receptor mRNAs in a manner consistent with a greater capacity to manage against oxidative damage, maintain cellular redox balance, and have a better control of protein-folding in the pituitaries of OSe and MIX versus ISe steers. In the liver, expression of 5 selenoprotein mRNA was affected (P ≤ 0.05) in a manner consistent with MIX steers having greater redox signaling capacity and capacity to manage oxidative damage than ISe steers. We conclude that inclusion of 3 mg Se/d as OSe or MIX versus ISe, forms of supplemental Se in vitamin-mineral mixes alters the selenoprotein transcriptome in a beneficial manner in both the pituitary and liver of growing steers consuming toxic endophyte-infected tall fescue.